Young student's motivations to choose an undergraduate midwifery program. Issue 3 (June 2016) - Cullen, D.; Sidebotham, M.; Gamble, J.; Fenwick, J.
Abstract: Background: Within the context of an ageing health workforce it is important to gain a greater understanding of the motivations of young people (aged less than 21 years) to choose a career in midwifery. Aim: To explore the reasons why young students decided to study midwifery and enrol in one Australian Bachelor of Midwifery program. Method: A descriptive exploratory qualitative design was used. Eleven midwifery students aged less than 21 years on enrollment participated in a semi-structured tape-recorded interview. The transcribed interviews were analysed using thematic analysis. Findings: Direct and indirect exposure to positive constructions of childbirth as well as the midwives role fuelled young student's fascination with midwifery and drove their desire to enrol. While some young students entered midwifery studies as a result of their 'love of babies' others took a more pragmatic 'wait and see' approach about their career choice. Many young students however clearly distinguished midwifery from nursing demonstrating an intention to be a midwife rather than a nurse. This decision often took place within the context of opposition from within their family, school and social networks where the public discourse continued to reinforce nursing as the preferred pathway to midwifery. Conclusion: Creating opportunities for young people to be exposed to positive constructions of childbirth as well as midwifery role models may increase the number of young students entering midwifery. There is also a need for information to be provided to school careers officers to assist them to understand the distinction between midwifery and nursing.